ANALISIS STRUKTUR PENDAPATAN ASLI DAERAH (PAD) PROVINSI BANTEN (ANALYSIS OF ORIGINAL LOCAL GOVERNMENT REVENUES (PAD) STRUCTURES OF BANTEN PROVINCE) - Moh Sofyan Budiarto (Inovasi, 2017)
Original Local Goverment Revenue (PAD) is still a major source of development financing in Banten Province obtained from local taxes, regional retribution, profits from regionally-owned enterprises (BUMD), and other legitimate sources of PAD. The purpose of this study is to analyze the structure of the Revenue component of the Region in accordance with the type and size of its contribution. This research uses descriptive qualitative method by utilizing data realization of Banten Province Revenue year 2013 -2016. The results show that the average contribution of PAD to Regional Revenue 2013-2016 is 66% to become the largest followed by Balance Fund equal to 22% and other valid Revenue equal to 12%. Local Taxes contributed the highest average of 95.5% to the PAD structure, followed by regional levy of 1.3%, and local financial management by 1% and other valid PAD of 2.2%. Of the components of Regional Taxes, Motor Vehicle Name Fee (BBNKB) (41%) and Motor Vehicle Tax (PKB) (34%) became the two largest contributions to the original income of the province of Banten. Public service levies accounted for the highest contribution (88.1%) of retribution followed by business services levies (6.6%) and user fees (5.3%).Keywords: regional local government revenues, local tax, local retribution, transfer of motor vehicle fee